High-reflection plastic aluminum mirror with high film-substrate binding force and preparation method of high-reflection plastic aluminum mirror
By magnetic sputtering titanium and aluminum layer on the plastic base, the use of titanium crystal layers can be used to improve the adhesion and density of the aluminum layer to solve the problem of the existing high reflected mirrors that are easily degraded and attached under the environmental conditions. A high reflective and long -lived high -reflex plastic aluminum mirror is achieved.
Patent Information
- Application Number
- CN202411332823.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-28
AI Technical Summary
The existing high reflectors are prone to degradation under environmental conditions, have poor adhesion, and are fragile and have large weight, which limits their application.
The titanium and aluminum are deposited to the surface of the plastic base through magnetic sputtering, and the aluminum layer is used to improve the adhesion and density of the aluminum layer to avoid flaws such as pinhole, thereby increasing the mirror reflectance.
A high -reflecting plastic aluminum mirror with high -film base combination is realized, the mirror reflectance and service life are improved, and the problem of fragile and heavy weight of glass substrate is solved.
Smart Images

Figure CN119372602A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of film coating, and in particular to a high-reflection plastic aluminum mirror with high film-base bonding strength and a preparation method thereof. Background Art
[0002] Highly reflective mirror coatings refer to coatings with high mirror reflectivity in the wavelength range of 380nm to 2000nm. Reflectors made of such coatings are widely used in lighting engineering and solar concentrators. Such reflectors not only have high mirror reflectivity and long service life under extreme weather conditions (ultraviolet radiation, chemical pollutants, moisture), but also should be cost-effective to produce and install under ideal circumstances.
[0003] Highly reflective mirrors are usually made by depositing metal reflective materials on the surface of a substrate. Therefore, some researchers have tried to use silver as a reflective metal because it has a high reflectivity of 96% in the range of 380-800 nm. However, silver-based surface mirrors are easily degraded when exposed to environmental conditions, and they have poor adhesion to certain substrates and lose their gloss due to sulfidation and chlorination, which greatly limits their application in actual production. Although the reflectivity of metallic aluminum is not as good as silver (91% in the range of 380-800nm), it is cheaper and more weather-resistant.
[0004] In this context, patent CN00130782.7 discloses a reflector, which forms a reflective film by sequentially depositing Al, MgF2, and TiO2 layers on a polished glass substrate. However, the Al layer deposited on the glass has poor adhesion and is prone to defects such as pinholes, which seriously affects the quality of the mirror surface and reduces the reflectivity of the mirror surface to light. The free ions in the glass substrate will corrode the Al layer and reduce the service life of the mirror surface. In addition, the glass substrate is usually heavy and fragile, which makes handling and installation an expensive and delicate process.
[0005] Magnetron sputtering is a physical vapor deposition technology commonly used for thin film deposition. It can produce thin films with excellent crystallinity, density and precise composition control. Plastic is a material made of polymer compounds, which has the characteristics of good chemical stability and strong plasticity. Mirrors made by sputtering coating with plastic as the substrate have good properties of high hardness, light weight, low cost and high durability. It matches the performance characteristics of glass mirrors, and the use of plastic mirrors will not be affected by transportation and installation related problems. However, the applicant found in preliminary experiments that the Al film produced by magnetron sputtering has poor adhesion to the plastic substrate, and the internal defects and pinhole-shaped flaws of the Al film greatly reduce the reflectivity and service life of the reflector. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a highly reflective plastic aluminum mirror with high film-base bonding strength and a preparation method thereof. The present invention deposits titanium and aluminum sequentially onto the surface of a plastic substrate by magnetron sputtering. The present invention not only finds that the titanium seed layer located in the middle can greatly improve the adhesion of the aluminum layer, but also finds that the titanium seed layer can effectively reduce the surface roughness of the aluminum layer, avoiding defects such as pinholes, thereby improving the mirror reflectivity.
[0007] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a highly reflective plastic aluminum mirror with high film-substrate bonding strength, which comprises a plastic substrate, a titanium seed layer and a highly reflective aluminum layer sequentially deposited on the surface of the plastic substrate by magnetron sputtering.
[0008] The growth mode of the high-reflection aluminum layer is a layer-island combination growth mode; the aluminum grain size in the high-reflection aluminum layer is ≥100nm; and the surface roughness of the high-reflection aluminum layer is <3nm.
[0009] The present invention deposits titanium and aluminum on the surface of a plastic substrate in sequence by magnetron sputtering, and the titanium seed layer in the obtained aluminum mirror is used as an intermediate layer. The present invention finds that the titanium seed layer can not only greatly improve the adhesion of the aluminum layer, but also effectively reduce the surface roughness of the aluminum layer, avoid defects such as pinholes, and thus improve the mirror reflectivity.
[0010] The specific principles are: For the enhancement of the film-based bonding force: Most plastics have high reactivity on the interface with Ti. Ti reacts with most functional groups of plastics to form a large number of C-Ti and (CO)-Ti bonds, while Al shows selective reactivity and only forms (CO)-Al bonds with some plastics containing carbonate groups, thus enhancing the adhesion. The reflectivity of this high-reflective film system in the visible light band can be higher than 92%, while the visible light reflectivity of a single-layer aluminum film made under the same process is only 81%.
[0011] Regarding the improvement of reflectivity: First, the sputtering threshold energy of the titanium seed layer is higher than that of aluminum, and the titanium seed layer is denser and harder. Compared with the plastic substrate, it can provide a higher surface energy interface for the subsequently deposited aluminum layer, resulting in reduced diffusion of aluminum on the seeding substrate, more nucleation sites, and reduced pinhole defects on the surface of the aluminum layer. Secondly, due to the Al-Al bond (264 kJ mol −1 ) and Ti-Al bonds (263 kJ mol −1 ) The similar dissociation energy of the two can lead to the growth of the aluminum layer in a layer-island bonding mode and the reduction of surface roughness. Finally, the present invention found that the size of the aluminum grains deposited on the surface of the titanium seed layer is larger than that of the sample without the titanium seed layer. The larger the aluminum grain size, the fewer grain boundaries, the weakened grain boundary plasma resonance, and the reduced light scattering, thereby improving the reflectivity.
[0012] Preferably, the plastic substrate is selected from one or more of polycarbonate (PC), polymethyl methacrylate (PMMA), polyphenylene sulfide (PPS), polystyrene (PS) and polyethylene terephthalate (PET); more preferably, polycarbonate (PC). PC not only has high strength and excellent heat resistance, but also has good weather resistance and anti-aging properties, and can be used for a long time in outdoor environments without failure.
[0013] In a second aspect, the present invention provides a method for preparing a highly reflective plastic aluminum mirror with high film-base bonding strength, which specifically comprises the following steps: 1) Cleaning of the surface of the plastic substrate.
[0014] 2) Under inert conditions, magnetron sputtering is used to remove the oxide layer on the surface of titanium and aluminum targets and plasma activate the surface of plastic substrates.
[0015] 3) Depositing a titanium seed layer on the surface of the plastic substrate by magnetron sputtering.
[0016] 4) Depositing a highly reflective aluminum layer on the surface of the titanium seed layer by magnetron sputtering.
[0017] Preferably, in step 1), the cleaning treatment comprises: removing oil stains on the surface of the plastic substrate by chemical reagents and water ultrasonic cleaning respectively, and drying and baking by cold air and hot air.
[0018] Preferably, in step 1), the chemical reagent is anhydrous ethanol, isopropanol or acetone, more preferably isopropanol.
[0019] Preferably, in step 1), the drying temperature is 60-80° C. and the drying time is 120-240 min.
[0020] Preferably, step 2) specifically comprises: fixing the plastic substrate on a base frame in a closed unbalanced magnetron sputtering coating machine, evacuating the vacuum; filling with inert gas, and first sputtering the titanium target, aluminum target and plastic substrate with high negative bias and low current.
[0021] The high negative bias voltage is 200-500V. If the bias voltage is too low, the ion cleaning of the substrate cannot be achieved. If the bias voltage is too high, the energy of the particles impacting the substrate is too high, and the surface of the substrate is easily damaged by heating. The low current is 0.2-0.4A. If the current is too low, the target material is not easy to ignite. If the current is too high, the substrate will undergo a sputtering deposition process.
[0022] Preferably, in step 2), the power supply on the target of the closed unbalanced magnetron sputtering coating machine is a DC power supply; the negative bias power supply on the base frame is a pulse power supply with a frequency of 200-300 Hz and a pulse width of 400-600 μs.
[0023] Preferably, in step 2), the vacuum degree after evacuation is 6.5×10 -6 -8.5×10 -6 torr; the temperature is room temperature; the inert gas argon has a flow rate of 20-40 sccm; the rotation speed of the base frame is 3-5 r / min; and the sputtering treatment time is 10-20 min.
[0024] Because aluminum is easily oxidized to aluminum oxide by oxygen in the atmosphere when deposited under low vacuum conditions, high vacuum conditions are sufficient to ensure the formation of a pure aluminum layer. In addition, too low working pressure is not conducive to target ignition, and too high pressure will cause the sputtered atoms to lose energy after colliding with argon atoms in the cavity, and cannot spontaneously migrate to the surface defects of the film after reaching the substrate, resulting in poor film quality. The rotation speed of the base frame within the above range is conducive to improving the uniformity of thin film deposition.
[0025] Preferably, in step 3), the current is 1.5-2.0 A, the negative bias voltage is 60-100 V, and the time is 8-20 min.
[0026] If the current is too low, the number of sputtered atoms will be small and the energy will be low, the film deposition rate will be slow, and the low-energy atoms reaching the substrate will not be able to spontaneously migrate to the surface defects. On the contrary, if the current is too high, the number of sputtered atoms will increase, the temperature inside the cavity will rise sharply with the deposition time, and the plastic substrate structure will be easily damaged.
[0027] Preferably, in step 3), after sputtering is completed, the current is adjusted back to 0.2-0.4 A. The purpose is to protect the titanium target and prevent the subsequent aluminum layer from being deposited on the surface of the titanium target.
[0028] Preferably, in step 4), target sputtering deposition is used, which is beneficial to improving the deposition rate and the density of the aluminum film; the current is 1.0-3.0A, the negative bias voltage is 60-100V, and the time is 2-10min.
[0029] Preferably, in step 4), after sputtering is completed, the current and voltage are turned off, the gas flow rate is lowered to 5-10 torr, and after 10-15 minutes, the coating process is turned off. This is because after the deposition, the temperature in the chamber is slightly high, and a small amount of argon gas is introduced to prevent oxidation of the aluminum film.
[0030] Compared with the prior art, the beneficial effects of the present invention are: (1) The present invention ingeniously deposits titanium and aluminum onto the surface of a plastic substrate in sequence by magnetron sputtering. The present invention not only finds that the titanium seed layer in the middle can greatly improve the adhesion of the aluminum layer, but also finds that the titanium seed layer can improve the density of the aluminum layer, reduce the surface roughness of the aluminum layer, avoid defects such as pinholes, and thus improve the mirror reflectivity.
[0031] (2) The plastic aluminum mirror of the present invention has the good properties of being strong, light, low cost and highly durable, and the use of the plastic mirror will not be affected by problems related to transportation and installation. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the internal principle diagram of the magnetron sputtering coating machine used in the present invention.
[0033] Figure 2 It is a schematic structural diagram of the high-reflective plastic aluminum mirror of the present invention.
[0034] Figure 3 The reflection spectra of Examples 2, 3, 4, 5 and 6 in the wavelength range of 380-800 nm.
[0035] Figure 4 The reflection spectra of Examples 1, 2 and 7 in the wavelength range of 380-800 nm.
[0036] Figure 5 It is the reflection spectrum of comparative example 1 and embodiment 1 in the wavelength range of 380-800nm.
[0037] Figure 6 SEM images of highly reflective plastic aluminum mirrors: (a) Comparative Example 1 and (b) Example 1.
[0038] Figure 7 Highly reflective plastic aluminum mirror for AFM 1 × 1µm 2 3D images of the scanned area: (a) Comparative Example 1 and (b) Example 1.
[0039] Figure 8 Optical images after the high-reflection plastic aluminum mirror tape peeling experiment: (a) Comparative Example 1 and (b) Example 1.
[0040] Fig. 9 Digital photos of the high-reflective plastic aluminum mirrors of Comparative Example 1 (left) and Example 1 (right). DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the embodiments.
[0042] Overall embodiment First, a highly reflective plastic aluminum mirror with high film-base bonding strength comprises a plastic substrate, a titanium seed layer and a highly reflective aluminum layer sequentially deposited on the surface of the plastic substrate by magnetron sputtering.
[0043] The growth mode of the high-reflection aluminum layer is a layer-island combination growth mode; the aluminum grain size in the high-reflection aluminum layer is ≥100nm; and the surface roughness of the high-reflection aluminum layer is <3nm.
[0044] In some preferred implementation cases, the plastic substrate is selected from one or more of polycarbonate (PC), polymethyl methacrylate (PMMA), polyphenylene sulfide (PPS), polystyrene (PS) and polyethylene terephthalate (PET); more preferably, polycarbonate (PC).
[0045] Secondly, a method for preparing a highly reflective plastic aluminum mirror with high film-base bonding strength comprises the following steps: 1) Cleaning of the surface of the plastic substrate.
[0046] In some preferred implementation cases, in step 1), the cleaning treatment includes: removing oil stains on the surface of the plastic substrate by using chemical reagents and water ultrasonic cleaning, respectively, and drying by cold air, hot air and drying. Further preferably, the chemical reagent is anhydrous ethanol, isopropanol or acetone, and isopropanol is further preferred. Further preferably, the drying temperature is 60-80°C and the drying time is 120-240min.
[0047] 2) Under inert conditions, magnetron sputtering is used to remove the oxide layer on the surface of titanium and aluminum targets and plasma activate the surface of plastic substrates.
[0048] In some preferred implementation cases, step 2) specifically includes: fixing the plastic substrate on a base frame in a closed unbalanced magnetron sputtering coating machine, evacuating the vacuum, filling with inert gas, and first sputtering the titanium target, aluminum target and plastic substrate with a high negative bias voltage and a low current. The high negative bias voltage is 200-500V; the low current is 0.2-0.4A.
[0049] In some more preferred implementation cases, the power supply on the target material of the closed unbalanced magnetron sputtering coating machine is a DC power supply, and the negative bias power supply on the base frame is a pulse power supply with a frequency of 200-300 Hz and a pulse width of 400-600 μs.
[0050] In some more preferred implementation cases, the vacuum degree after evacuation is 6.5×10 -6 -8.5×10 - 6 torr; the temperature is room temperature; the inert gas argon has a flow rate of 20-40 sccm; the rotation speed of the base frame is 3-5 r / min; and the sputtering treatment time is 10-20 min.
[0051] 3) Depositing a titanium seed layer on the surface of the plastic substrate by magnetron sputtering.
[0052] In some preferred implementation cases, in step 3), the current is 1.5-2.0 A, the negative bias voltage is 60-100 V, and the time is 8-20 min.
[0053] In some more preferred implementation cases, in step 3), after sputtering is completed, the current is adjusted back to 0.2-0.4 A. The purpose is to protect the titanium target and prevent the subsequent aluminum layer from being deposited on the surface of the titanium target.
[0054] 4) Depositing a highly reflective aluminum layer on the surface of the titanium seed layer by magnetron sputtering.
[0055] In some preferred implementation cases, in step 4), target sputtering deposition is adopted; the current is 1.0-3.0A, the negative bias voltage is 60-100V, and the time is 2-10min.
[0056] In some more preferred implementation cases, in step 4), after the sputtering is completed, the current and voltage are turned off, the gas flow rate is lowered to 5-10 torr, and after continuing for 10-15 minutes, the coating process is turned off.
[0057] Specific Examples and Comparative Examples Comparative Example 1 (1) The PC substrate was ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature: 70 °C, time: 180 min). It was then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 7.5 × 10 -6 torr; (2) At room temperature, argon gas was filled in with a flow rate of 30 sccm, the turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs, and the target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the aluminum target and the plasma activation on the surface of the plastic substrate; (3) The current of the aluminum target sputtering was changed to 2.21A and the negative bias voltage was changed to 80V. A layer of highly reflective aluminum was sputtered on the PC substrate for 3 minutes. After the sputtering process was completed, the current and voltage were turned off, the argon gas flow rate was adjusted to 10 sccm, and the duration was 10 minutes. Then, the coating program was turned off and the chamber was taken out after cooling to room temperature.
[0058] Example 1 (1) The PC substrate was ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature: 70 °C, time: 180 min). It was then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 7.5 × 10 -6 torr; (2) At room temperature, argon gas was filled in with a flow rate of 30 sccm, the turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs, and the target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the titanium target and the aluminum target and the plasma activation on the surface of the plastic substrate; (3) Change the current on the titanium target to 1.67 A and the negative bias voltage to 80 V, first sputter a titanium seed layer for 14 min, and then adjust the current of the titanium target back to 0.3 A; (4) The current of the aluminum target sputtering was changed to 2.21A and the negative bias voltage was changed to 80V. A highly reflective aluminum layer was sputtered on the titanium seed layer for 3 minutes. After the sputtering process was completed, the current and voltage were turned off, the argon gas flow rate was adjusted to 10 sccm, and the duration was 10 minutes. Then, the coating program was turned off and the chamber was taken out after cooling to room temperature.
[0059] Example 2 (1) The PC substrate was ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature: 70 °C, time: 180 min). It was then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 7.5 × 10 -6 torr; (2) At room temperature, argon gas was filled in with a flow rate of 30 sccm, the turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs, and the target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the titanium target and the aluminum target and the plasma activation on the surface of the plastic substrate; (3) Change the current on the titanium target to 1.67 A and the negative bias voltage to 80 V, first sputter a titanium seed layer for 14 min, and then adjust the current of the titanium target back to 0.3 A; (4) The current of the aluminum target sputtering was changed to 1.71A and the negative bias voltage was changed to 80V. A highly reflective aluminum layer was sputtered on the titanium seed layer for 3 minutes. After the sputtering process was completed, the current and voltage were turned off, the argon gas flow rate was adjusted to 10 sccm, and the duration was 10 minutes. Then, the coating program was turned off and the chamber was taken out after cooling to room temperature.
[0060] Example 3 (1) The PC substrate was ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature: 70 °C, time: 180 min). It was then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 7.5 × 10 -6 torr; (2) At room temperature, argon gas was filled in with a flow rate of 30 sccm, the turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs, and the target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the titanium target and the aluminum target and the plasma activation on the surface of the plastic substrate; (3) Change the current on the titanium target to 1.67 A and the negative bias voltage to 80 V, first sputter a titanium seed layer for 14 min, and then adjust the current of the titanium target back to 0.3 A; (4) The current of the aluminum target sputtering was changed to 1.71A and the negative bias voltage was changed to 80V. A highly reflective aluminum layer was sputtered on the titanium seed layer for 4 minutes. After the sputtering process was completed, the current and voltage were turned off, the argon gas flow rate was adjusted to 10 sccm, and the duration was 10 minutes. Then, the coating program was turned off and the chamber was taken out after cooling to room temperature.
[0061] Example 4 (1) The PC substrate was ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature: 70 °C, time: 180 min). It was then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 7.5 × 10 -6 torr; (2) At room temperature, argon gas was filled in with a flow rate of 30 sccm, the turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs, and the target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the titanium target and the aluminum target and the plasma activation on the surface of the plastic substrate; (3) Change the current on the titanium target to 1.67 A and the negative bias voltage to 80 V, first sputter a titanium seed layer for 14 min, and then adjust the current of the titanium target back to 0.3 A; (4) The current of the aluminum target sputtering was changed to 1.71A and the negative bias voltage was changed to 80V. A highly reflective aluminum layer was sputtered on the titanium seed layer for 5 minutes. After the sputtering process was completed, the current and voltage were turned off, the argon gas flow rate was adjusted to 10 sccm, and the duration was 10 minutes. Then, the coating program was turned off and the chamber was taken out after cooling to room temperature.
[0062] Example 5 (1) The PC substrate was ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature: 70 °C, time: 180 min). It was then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 7.5 × 10 -6 torr; (2) At room temperature, argon gas was filled in with a flow rate of 30 sccm, the turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs, and the target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the titanium target and the aluminum target and the plasma activation on the surface of the plastic substrate; (3) Change the current on the titanium target to 1.67 A and the negative bias voltage to 80 V, first sputter a titanium seed layer for 14 min, and then adjust the current of the titanium target back to 0.3 A; (4) The current of the aluminum target sputtering was changed to 1.71A and the negative bias voltage was changed to 80V. A highly reflective aluminum layer was sputtered on the titanium seed layer for 6 minutes. After the sputtering process was completed, the current and voltage were turned off, the argon gas flow rate was adjusted to 10 sccm, and the duration was 10 minutes. Then, the coating program was turned off and the chamber was taken out after cooling to room temperature.
[0063] Example 6 (1) The PC substrate was ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature: 70 °C, time: 180 min). It was then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 7.5 × 10 -6 torr; (2) At room temperature, argon gas was filled in with a flow rate of 30 sccm, the turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs, and the target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the titanium target and the aluminum target and the plasma activation on the surface of the plastic substrate; (3) Change the current on the titanium target to 1.67 A and the negative bias voltage to 80 V, first sputter a titanium seed layer for 14 min, and then adjust the current of the titanium target back to 0.3 A; (4) The current of the aluminum target sputtering was changed to 1.71A and the negative bias voltage was changed to 80V. A highly reflective aluminum layer was sputtered on the titanium seed layer for 7 minutes. After the sputtering process was completed, the current and voltage were turned off, the argon gas flow rate was adjusted to 10 sccm, and the duration was 10 minutes. Then, the coating program was turned off and the chamber was taken out after cooling to room temperature.
[0064] Example 7 (1) The PC substrate was ultrasonically cleaned with isopropyl alcohol and deionized water for 15 min, dried with cold and hot air, and dried in a hot oven (temperature: 70 °C, time: 180 min). It was then fixed on the base stand of a closed unbalanced magnetron sputtering device (UDP-650). After rough vacuuming with a mechanical pump, the vacuum degree was pumped to 7.5 × 10 -6 torr; (2) At room temperature, argon gas was filled in with a flow rate of 30 sccm, the turntable speed was set to 4 r / min, the frequency of the pulse bias power supply was set to 250 Hz and the pulse width was set to 500 μs, and the target and substrate were first sputtered and cleaned for 10 min with a negative bias voltage of 200 V and a low current of 0.3 A to remove the oxide layer on the surface of the titanium target and the aluminum target and the plasma activation on the surface of the plastic substrate; (3) Change the current on the titanium target to 1.67A and the negative bias voltage to 80V, first sputter a titanium seed layer, the sputtering time is 14min, and the thickness is 110nm. Then adjust the current of the titanium target back to 0.3A; (4) The current of the aluminum target sputtering was changed to 1.21A and the negative bias voltage was changed to 80V. A highly reflective aluminum layer was sputtered on the titanium seed layer for 3 minutes with a thickness of 40nm. After the sputtering process was completed, the current and voltage were turned off, the argon gas flow rate was adjusted to 10sccm for 10 minutes, and then the coating program was turned off and the chamber was taken out after cooling to room temperature.
[0065] Performance Testing and Characterization The following is the tested data: Figure 1 The internal principle diagram of the closed unbalanced magnetron sputtering coating machine used in the present invention. Figure 1 As shown, the coating machine has four target positions, two aluminum targets are installed opposite to each other, and the titanium target is installed on the right. The sample is installed and fixed on the base frame in the middle. During the experiment, the base frame rotates, and the low-temperature and high-speed coating deposition process is achieved by controlling the current, voltage and negative bias voltage on the base frame.
[0066] Figure 2Schematic diagram of the structure of the high-reflection plastic aluminum mirror of the present invention. Figure 2 As shown, the structure is a multi-layer film structure. A titanium seed layer with strong adhesion and high surface energy is first deposited on the surface of the PC substrate, and then a high-reflection aluminum layer is deposited to obtain a high-reflection plastic aluminum mirror with strong film-base bonding. The structure is simple and suitable for mass production.
[0067] Figure 3 is the reflection spectrum of Examples 2, 3, 4, 5 and 6 in the range of 380-800 nm. Figure 3 As shown, the plastic aluminum mirror in Example 2 has the highest visible light reflectivity, which is 86%; the plastic aluminum mirrors in Examples 3, 4 and 5 have visible light reflectivity of 82%, 79% and 75% respectively; and the plastic aluminum mirror in Example 6 has the lowest visible light reflectivity, which is only 65%. The results show that under the same other deposition processes, the visible light reflectivity of the plastic aluminum mirror decreases significantly as the deposition time of the high-reflection aluminum layer increases.
[0068] Figure 4 is the reflection spectrum of Examples 1, 2 and 7 in the wavelength range of 380-800nm. Figure 4 As shown in the figure, the plastic aluminum mirror in Example 1 has the highest reflectivity, which is 92.4%; the visible light reflectivity of the plastic aluminum mirrors in Examples 2 and 7 is 86.7% and 81.2%. This is because as the aluminum target sputtering current increases, the number and kinetic energy of the sputtered aluminum atoms increase, the film deposition rate increases, and the aluminum atoms have enough kinetic energy to spontaneously migrate to the surface defects after reaching the surface of the titanium seed layer, making the film denser and more reflective. The results show that as the aluminum target sputtering current increases, the visible light reflectivity of the double-layer film structure increases significantly.
[0069] Figure 5 : is the reflection spectrum of Comparative Example 1 and Example 1 in the range of 380-800nm. Figure 5 As shown, the visible light reflectivity in Comparative Example 1 is 81.9%, while the visible light reflectivity of the film layer in Example 1 is significantly improved to 92.4%. Under the same aluminum coating process conditions, the increase in visible light reflectivity is attributed to the addition of the titanium seed layer. The results show that the addition of the titanium seed layer can significantly improve the visible light reflectivity of the aluminum film.
[0070] Figure 6 The following are SEM images of plastic reflectors: (a) Comparative Example 1 and (b) Example 1. Figure 6As shown, the single grains on the surface layer of the single-layer aluminum film (Al) in Comparative Example 1 are small and clearly visible, with obvious grain boundaries and obvious light-dark contrast changes. In contrast, the surface of the aluminum film with a titanium seed layer in Example 1 is smooth and dense, with unclear grain boundaries and no obvious light-dark contrast changes. This shows that the aluminum film in Comparative Example 1 grows in accordance with the Volmer-Weber model, that is, the initial growth mode is isolated islands, which leads to an increase in the surface roughness of the aluminum film. In Example 1, due to Al-Al (264 kJ mol −1 ) and Ti-Al (263 kJ mol −1 ) causes the growth mode of the aluminum film to change from island growth to layer-island combination growth mode, which reduces the surface roughness. This is also related to the aluminum (1.160 J m −2 ) is related to the surface free energy of the film deposition surface, titanium (1.989 J m −2 ) is significantly higher than the surface free energy of pristine polycarbonate (0.38 J m −2 ), Example 1 deposits aluminum on a titanium seed layer with high surface free energy, the diffusion of aluminum atoms on the substrate is reduced, and there are more nucleation sites. The particle size range of the aluminum grains in Comparative Example 1 is 90-120nm, while the particle size range of the aluminum grains in Example 1 is 100-130nm, as measured by Nano Measurer software. The grain size increases, the grain boundaries decrease, and the grain boundary plasma resonance on the surface of the film causes the scattering of light to be weakened, thereby increasing the reflectivity of the film. The results show that the addition of a titanium seed layer leads to a more layered growth mechanism, the surface roughness of the film is reduced, the nucleation sites are increased, and the diffusion of aluminum atoms is reduced; while the grain size increases, the grain boundaries decrease, the scattering of light caused by the grain boundary plasma resonance is reduced, and the reflectivity of the film is improved.
[0071] Figure 7 Highly reflective plastic aluminum mirror for AFM 1×1µm 2 3D images of the scanned area: (a) Comparative Example 1 and (b) Example 1. Figure 7 As shown, the surface of the sample in Comparative Example 1 is uneven and has a large number of sharp protrusions. Compared with Comparative Example 1, the sample in Example 1 is relatively flat, with almost no sharp protrusions on the surface. The surface roughness of the sample in Comparative Example 1 was Ra=2.2nm measured by Nanoscope Analysis, while the surface roughness of the sample in Example 1 was Ra=1.8nm. This shows that the initial growth mode of the aluminum film in Comparative Example 1 was isolated islands, and the growth of each isolated island caused the roughness to increase. In Example 1, due to the tight bond energy of Al-Al (264 kJ mol−1) and Ti-Al (263 kJ mol−1), the growth mode of the aluminum film changed from island growth to layer-island combined growth mode. This more layered growth mode caused the surface roughness of the film to decrease. Figure 7 The scanned area in (a) also shows Figure 7 (b) Smaller grain size of the sample. The grain size decreases, the grain boundaries increase, and the grain boundary plasma resonance on the film surface leads to enhanced light scattering, which results in a decrease in the film reflectivity in Comparative Example 1. The results show that the addition of a titanium seed layer leads to a more layered growth mechanism, and the surface roughness of the film decreases; while the grain size increases, the grain boundaries decrease, the grain boundary plasma resonance causes less light scattering, and the film reflectivity increases.
[0072] Figure 8 Optical images of plastic reflector after tape peeling experiment: (a) Comparative Example 1 and (b) Example 1. Figure 8 As shown, the samples in Comparative Example 1 fell off in large quantities after the tape stripping test, with only a small amount of adhesion at the edges, and the surface density of the film was poor, with a large number of pinhole-shaped defects. Compared with Comparative Example 1, the sample in Example 1 did not fall off after the tape stripping test, and the surface of the film was smooth and dense, without obvious defects or flaws. This is because the sputtering threshold energy of the titanium seed layer is higher than that of aluminum, and the titanium seed layer is denser and has a high hardness. Compared with the plastic substrate in Comparative Example 1, the titanium seed layer provides a higher surface energy interface for the subsequently deposited aluminum film, which leads to reduced diffusion of aluminum on the seeding substrate, more nucleation sites, and reduced pinhole-shaped defects on the surface of the aluminum film. The results show that the addition of a titanium seed layer can not only improve the film-base bonding between the aluminum film and the plastic substrate, but also improve the density of the film and reduce pinhole-shaped defects.
[0073] Fig. 9 The following are digital photos of the plastic aluminum mirrors of Comparative Example 1 (left) and Example 1 (right). Fig. 9 As shown, the surface of the plastic aluminum mirror in comparative example 1 is slightly yellowish and has a low glossiness, while the plastic aluminum mirror in embodiment 1 is bright silver-white and has a significantly improved glossiness. The results show that the addition of the titanium seed layer can improve the glossiness of the aluminum film.
[0074] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0075] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A highly reflective plastic aluminum mirror with high film-base bonding strength, characterized in that: It comprises a plastic substrate, a titanium seed layer and a high-reflection aluminum layer deposited on the surface of the plastic substrate in sequence by magnetron sputtering; The growth mode of the high reflective aluminum layer is a layer-island combined growth mode; The aluminum grain size in the highly reflective aluminum layer is ≥100 nm; The surface roughness of the high-reflection aluminum layer is less than 3 nm.
2. The highly reflective plastic aluminum mirror with high film-base bonding strength according to claim 1, characterized in that: The plastic substrate is selected from one or more of polycarbonate, polymethyl methacrylate, polyphenylene sulfide, polystyrene and polyethylene terephthalate.
3. The highly reflective plastic aluminum mirror with high film-base bonding strength according to claim 2, characterized in that: The plastic substrate is polycarbonate.
4. A method for preparing a highly reflective plastic aluminum mirror with high film-base bonding strength according to any one of claims 1 to 3, characterized in that include: 1) Cleaning of the surface of the plastic substrate; 2) Under inert conditions, magnetron sputtering is used to remove the oxide layer on the surface of titanium and aluminum targets and plasma activate the surface of plastic substrates; 3) depositing a titanium seed layer on the surface of the plastic substrate by magnetron sputtering; 4) Depositing a highly reflective aluminum layer on the surface of the titanium seed layer by magnetron sputtering.
5. The preparation method according to claim 4, characterized in that: In step 1), the cleaning treatment includes: removing oil stains on the surface of the plastic substrate by using chemical reagents and water ultrasonic cleaning, and drying and baking by cold air and hot air.
6. The preparation method according to claim 4, characterized in that: Step 2) specifically includes: fixing the plastic substrate on a base frame in a closed unbalanced magnetron sputtering coating machine, evacuating the vacuum; filling with inert gas, and sputtering the titanium target, aluminum target and plastic substrate with high negative bias voltage and low current; The high negative bias voltage is 200-500V; the low current is 0.2-0.4A.
7. The preparation method according to claim 4, characterized in that: In step 3), the current is 1.5-2.0A, the negative bias voltage is 60-100V, and the time is 8-20min.
8. The preparation method according to claim 4 or 7, characterized in that: In step 3), after sputtering is completed, the current is adjusted back to 0.2-0.4A.
9. The preparation method according to claim 4, characterized in that: In step 4), target sputtering deposition is adopted; the current is 1.0-3.0A, the negative bias voltage is 60-100V, and the time is 2-10min.
10. The preparation method according to claim 4 or 9, characterized in that: In step 4), after sputtering is completed, turn off the current and voltage, lower the gas flow rate to 5-10 torr, and continue for 10-15 minutes before turning off the coating program.
Citation Information
Patent Citations
Reflecting mirror and projecting display therefor
CN1150418C